2012
DOI: 10.1097/opx.0b013e31826c1831
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pupil Diameter on Axial Growth in Orthokeratology

Abstract: Large pupil diameters facilitate the effect of OK to slow axial growth in myopia. We speculate that this is because of enhancement of the myopic shift in the peripheral retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 22 publications
5
83
1
3
Order By: Relevance
“…Conversely, Santodomingo‐Rubido et al found no significant correlation between corneal HOA changes and axial elongation after three and 24 months of orthokeratology in European children. Chen et al found that a larger pupil size during orthokeratology treatment in Chinese children was associated with slower axial eye growth than a smaller pupil, and suggested that this is due to a greater relative peripheral myopic shift. This change in peripheral refraction was confirmed with modelling by Faria‐Ribeiro et al, who also demonstrated that on‐ and off‐axis HOAs, particularly primary horizontal coma (Z31) and primary spherical aberration (Z40), also increase with greater pupil size as a result of corneal topographical changes during orthokeratology.…”
Section: Hoas and Myopia Control Interventionsmentioning
confidence: 99%
“…Conversely, Santodomingo‐Rubido et al found no significant correlation between corneal HOA changes and axial elongation after three and 24 months of orthokeratology in European children. Chen et al found that a larger pupil size during orthokeratology treatment in Chinese children was associated with slower axial eye growth than a smaller pupil, and suggested that this is due to a greater relative peripheral myopic shift. This change in peripheral refraction was confirmed with modelling by Faria‐Ribeiro et al, who also demonstrated that on‐ and off‐axis HOAs, particularly primary horizontal coma (Z31) and primary spherical aberration (Z40), also increase with greater pupil size as a result of corneal topographical changes during orthokeratology.…”
Section: Hoas and Myopia Control Interventionsmentioning
confidence: 99%
“…While other factors as increased effect of aberrations might be involved, the authors justified their findings with the fact that larger pupil size will enhance the effect caused by the peripheral corneal steepening on the myopization of the peripheral retina. 16 To this date, all the previous literature has analyzed the refractive outcomes of orthokeratology in terms of vectorial decomposition of refraction, while no study has paid attention to the relative field curvature of both extremes of the interval of Sturm represented by the tangential (F T ) and sagittal (F S ) focal lengths. The relative positions of the sagittal and tangential foci might be crucial to understand the mechanisms that guide the elongation of the eye.…”
Section: Introductionmentioning
confidence: 99%
“…At present, orthokeratology (OK) is the most effective non-pharmacological method in slowing down myopia progression compared to the use of single-vision spectacle lenses (SV) [3][4][5], bifocal spectacles [6], progressive addition lenses [7,8], soft lenses [9], and rigid gas-permeable contact lenses (RGP) [10]. However, the biggest challenge is to identify those children who may benefit from the use of OK. Investigators have tried to identify the factors affecting the efficacy of OK in myopic control such as initial age [11][12][13][14], spherical equivalent refractive errors (SER) [11][12][13][14][15], pupil diameter [13,16], age of myopia onset [13], myopia progression 2 years before baseline [13], anterior chamber depth [13], and parental refraction [13]. Myopia progression was estimated from changes in axial length (AL), which was evaluated using a noncontact optic biometric device (IOL Master).…”
Section: Introductionmentioning
confidence: 99%